Pengaruh Kualitas Produk dan Kepercayaan Terhadap Keputusan Pembelian Obat Herbal - Fatkhan, Regita Amalia; Mardikaningsih, Rahayu (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Purchasing herbal medicine is increasingly becoming a concern amidst increasing public awareness of the importance of health and preference for alternative treatments with minimal side effects. This literature study aims to examine the influence of product quality and trust on herbal medicine purchasing decisions. In this context, good product quality and consumer trust are important factors that can encourage people to choose herbal medicine as a safer and more effective option. This study applies a literature review method through analysis of various relevant scientific sources. The results of the study indicate that product quality and trust have a significant influence on herbal medicine purchasing decisions. The influence of product quality is very important, because quality products can increase consumer satisfaction and loyalty, while trust serves as a guarantee for consumers to choose products that are proven to be safe and have minimal side effects. Therefore, herbal medicine producers and related parties are expected to continue to improve product quality and build public trust to encourage positive purchasing decisions.